(untitled) (Bangladesh Journal of Neuroscience, 2013)
This cross sectional study was done from April 2005 to November 2009 in the department of Neurosurgery of Chittagong Medical College Hospital. We have studied 20 patients of D12, L1, L2 & L3 fracture with lower limb weakness. Data were collected by a brief history, clinical examination, surgery & postoperative follow up. Most of the sufferers were male (90.00%). The age groups were 21-40 years gripped the major proportion (50.00%) of the patients. The commonest causes of injury were fall from height (60.00%). The majority of patients had been suffering from L1 fracture (45.00%). The most (90.00%) of the sufferers had parapareses. The highest groups of patients (90.00%) improved after surgery. So, the study concludes that the anterolateral decompression, fusion & fixation is one of the best options of treatment of throracolumbar spine fracture. Bangladesh Journal of Neuroscience 2012; Vol. 28 (1): 24-28